Systemic and cognitive study of the influence of ecology on the quality of life - E. V. Lutsenko; T. P. Baranovskaya (Новые технологии)
A system-cognitive study provides the following scientific results: 1) information portraits of classes and values of factors; 2) SWOT-analysis of the influence of environmental factors on the parameters of quality of life; 3) cognitive class diagrams and cognitive diagrams of signs (factor values); 4) dendrograms of cognitive clustering of classes and values of factors; 5) non-local neurons and a layer of a non-local neural network; 6) 3d integral cognitive maps; 7) cognitive functions, reflecting how much information is contained in the values of environmental factors on the values of scales measuring the quality of life (classes); 8) cognitive diagrams of meaningful comparison of classes; 9) cognitive diagrams of meaningful comparison of the values of environmental factors on their impact on class membership; 10) Pareto curve of significance of gradations of descriptive scales, i.e. values of environmental factors.